Nanocrystal formation during thermal treatment of phosphoric-acid-swollen polybenzimidazole membranes - Ivanova, O.; Lüke, W.; Nemkovski, K.; Appavou, M.-S.; Szekely, N. K.; Pipich, V.; Frielinghaus, H.; Monkenbusch, M.; Zorn, R.; Lehnert, W.; Holderer, O. (Frontiers in Materials, 2023)
The design of suitable and efficient membranes for fuel and electrolyzer cells has been a long standing problem that still seeks for technical improvements. The structural properties of proton conducting poly [2,2-(m-phenylene)-5,5-bibenzimidazole] (PBI) membranes doped with phosphoric acid as electrolyte have been investigated prior and after thermal treatment by small angle neutron scattering (SANS), neutron diffraction with polarization analysis and transmission electron microscopy (TEM). Our observations indicate that during the first heating attempt stable crystalline domains in the PBI are formed and they persist in all further thermal cycles typical for electrolyte membrane operation. The combination of real space TEM picture under cryogenic conditions and reciprocal space scattering pattern with enhanced contrast by partial deuteration allows obtaining unique insight into the structure of proton conducting membranes, i.e., characteristic distances associated with irreversible changes as well as volume fraction of the different phases of the sample.